(untitled) (Legal journal - Research in Legal and Social Sciences, 2025)
This study examines the victimogenic elements that influence the reporting of gender-based violence in Cuba, from a social and cultural perspective. A mixed-methods approach was employed, utilizing a non-experimental and descriptive research design that integrated both theoretical and empirical methods. The theoretical methods included the historical-logical, analysis-synthesis, and inductive-deductive approaches. Among the empirical methods, documentary analysis, semi-structured interviews, and exegetical analysis of current legislation were applied. The findings reveal that economic dependency, fear of retaliation, social stigmatization, and distrust in the judicial system significantly hinder the reporting of such crimes. Furthermore, institutional barriers were identified that obstruct the effective protection of victims. The study concludes that the low reporting rate is the result of a complex web of structural factors, which require a comprehensive intervention strategy. Such a strategy should combine awareness-raising efforts, institutional strengthening, and legal reforms to ensure access to justice and victim protection. Understanding these results may inform future actions and policies aimed at effectively addressing the issue at hand.